EVALUASI PENERAPAN BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA PADA RUMAH SAKIT BERSTATUS BADAN LAYANAN UMUM (Studi Kasus pada Rumah Sakit Mata Cicendo Bandung) - Utami, Mega Putri; Hastuti, Hastuti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2018)
The purpose of this research is to know the performance measurement by using balanced scorecard approach which result can be used to evaluate the performance of a public organization. This research uses descriptive quantitative method with data collection technique using questionnaire method for sub customer perspective only and for the other perspective using documentation method. This research took data from 3 years, that is 2015, 2016, and 2017. The results showed that the performance of Rumah Sakit Mata Cicendo Bandung seen from (1). The growth and learning perspective of the employee capability indicator can be said to be good, but for employee retention indicators are still considered unfavorable. (2). The internal business process perspective is seen from the indicators of Medical Record Complete 24 hours of service, Medical Record Return, Blindness number â¥ 48 hours, and PODR shows good performance criteria, while the the other indicators show good criteria. (3). Customer perspective seen from customer retention indicator and customer acquisition indicate good enough criterion, while for the other indicator show good performance. (4). Financial perspective seen from indicator of liquidity and activity still indicate good criterion, while the indicator good enough criteria.Â Keywords: Balanced Scorecard, Performance Measurement, Hospital, Public Service Agency.